The evolution of wireless mobile networks and the future 5G mobile technology for sustainability. - Leliopoulos, Panagiotis; Drigas, Athanasios (Technium Sustainability, 2022)
In this paper, our study focused on the framework of big data-driven and mobile optimization. We will study the significant points of 5G and previous mobile networks, and mostly we have a look at past mobile technologies. After that, we will focus on the future 5G Mobile Technology. We will make an essential reference to the architecture of the 5G Mobile Network. We will see the two OSI levels (network level and Internet Protocol (IP)). The purpose of IP is to ensure adequate control data (in IP header) for proper routing of IP packets belonging to specific application connections or sessions between client and server applications somewhere on the Internet. Also, we mention the primary points of 5G. The device-based architectures, the millimeter-wave, the massive multiple inputs - multiple outputs, the smarter devices, and the manual support for machine-to-machine communication. Finally, in this paper, we will see how much faster will be the future 5G mobile network and services can support. Those services, including experience at speeds of at least 1 Gbps or higher, 10 Gbps data transfer, zero secondary switches, enormous capacity, and reduce power consumption, are the areas of 5G network we see in this study.